THE URGENCY OF ACCELERATING THE REALIZATION OF THE POLICY GUARANTEE PROGRAM AS AN EFFORT TO PROTECT THE INSURED DUE TO DEFAULT ON INSURANCE COMPANY CLAIMS - Seputro, Anang (JOURNAL EQUITABLE, 2026)
A series of cases of massive claim default, such as the one that befell PT Asuransi Jiwasraya with losses of more than sixteen trillion rupiah and PT Asuransi Jiwa Kresna which harmed thousands of policyholders, clearly reveal the absence of an effective and fast legal protection mechanism for the insured. This study aims to analyze the urgency of accelerating the implementation of the Policy Guarantee Program as a vital instrument of legal protection for policyholders, as well as evaluating the adequacy of the current regulatory framework. The research method used is normative juridical by integrating a legal approach, a conceptual approach, and a comparative legal. The results show that delays in program implementation have the potential to significantly increase the accumulation of policyholder losses and increase systemic risks in the financial services sector. Different from previous research which mostly focused on the urgency of establishing institutional aspects, this study provides a more advanced academic contribution in the form of formulation of concrete recommendations on the substance of Government Regulations that must be issued, including, among others, the determination of policy guarantee value limits, specific criteria for the level of financial health of the insurance companies participating in the program, and an integrated coordination mechanism between financial sector supervisory authorities. Thus, this study offers an applicative normative roadmap to ensure preventive and responsive legal protection before the official implementation deadline.